Enhanced Tetracycline Removal from Highly Concentrated Aqueous Media by Lipid-Free Chlorella sp. Biomass (2022)
Microalgae are used as a lipid source for different applications, such as cosmetics and biofuel. The nonliving biomass and the byproduct from the lipid extraction procedure can efficiently remove antibiotics. This work has explored the potential use of Chlorella sp. biomasses for tetracycline (Tc) removal from highly concentrated aqueous media. Non-living biomass (NLB) is the biomass before the lipid extraction procedure, while lipid-extracted biomass (LEB) is the byproduct mentioned before. LEB removed 76.9% of Tc at 40 mg/L initial concentration and 40 mg of biomass, representing an adsorption capacity of 19.2 mg/g. Subsequently, NLB removed 68.0% of Tc at 50 mg/L and 60 mg of biomass, equivalent to 14.2 mg/g of adsorptive capacity. These results revealed an enhanced removal capacity by LEB compared with NLB and other microalgae-based materials. On the other hand, the adsorption kinetics followed the pseudo-second-order and Elovich models, suggesting chemisorption with interactions between adsorbates. The adsorption isotherms indicate a multilayer mechanism on a heterogeneous surface. Additionally, the interactions between the surface and the first layer of tetracycline are weak, and the formation of the subsequent layers is favored. The Chlorella sp. biomass after the lipid extraction process is a promising material for removing tetracycline; moreover, the use of this residue contributes to the zero-waste strategy.